Recommendations of the Polish Society of Gynaecologists and Obstetricians, Polish Paediatric Society, Polish Society of Family Medicine, Polish Society of Vaccinology, Polish Society of Oncological Gynaecology, and Polish Society of Colposcopy and Pathophysiology of the Uterine Cervix on prophylactic vaccinations against infections with human papillomaviruses in Poland - Nowakowski, Andrzej; Jach, Robert; Szenborn, Leszek; Bidziński, Mariusz; Jackowska, Teresa; Kotarski, Jan; Mastalerz-Migas, Agnieszka; Nitsch-Osuch, Aneta; Pinkas, Jarosław; Sawicki, Włodzimierz; Sieroszewski, Piotr; Stukan, Maciej; et al. (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Several hundred million people are infected with genital genotypes of the human papillomavirus (HPV) annually in the world. The infections transmitted mainly through sexual routes are usually asymptomatic, but can lead to the development of cervical, vulvar, vaginal, anal, and penile cancers, some head and neck cancers, and genital warts (condylomas). The fraction HPV-related cancers ranges from nearly 100% in the case of cervical cancer to several/over a dozen percent in the case of other cancers and diseases. There are no effective drugs against HPV, but prophylactic HPV vaccines are available free of charge in immunization programmes in many countries around the world. In Poland, HPV vaccinations have so far been executed out of pocket or in free- of-charge, local-governmental prevention programmes, but the vaccination coverage of the target population does not exceed 10%. In November 2021, one of the vaccines became available with a 50% reimbursement, work is underway to reimburse the next ones, and the National Oncology Strategy assumes the implementation of the HPV immunization programmes and vaccination of 60% of the teenage population by 2028. Three prophylactic HPV vaccines are registered. All of them are safe and their effectiveness in the prevention of diseases caused by vaccine genotypes is almost 100%, provided that full post-vaccination immunity is obtained before contact with the virus. Girls aged 11–13 years are the priority target cohort for HPV vaccination in Poland. The implementation of routine, free-of-charge HPV immunization in the Preventive Immunization Programme (PIP) for all adolescents should be pursued. Persons over the age of 13 years may also benefit from HPV vaccination and should be vaccinated according to product specifications. In addition to free access under the PIP, the key element for the success of the implementation of HPV vaccinations in Poland will be the education of medical personnel and parents of adolescents to be vaccinated.